Genotoxin-producing Salmonella enterica induces tissue-specific types of DNA damage and DNA damage response outcomes - Lopez Chiloeches, Maria; Bergonzini, Anna; Martin, Océane C. B.; Bergstein, Nicole; Erttmann, Saskia F.; Aung, Kyaw Min; Gekara, Nelson O.; Avila Cariño, Javier F.; Pateras, Ioannis S.; Frisan, Teresa (Frontiers in Immunology, 2024)
Typhoid toxin-expressing Salmonella enterica causes DNA damage in the intestinal mucosa in vivo, activating the DNA damage response (DDR) in the absence of inflammation. To understand whether the tissue microenvironment constrains the infection outcome, we compared the immune response and DDR patterns in the colon and liver of mice infected with a genotoxigenic strain or its isogenic control strain.The presence of the typhoid toxin protected from colonic bacteria-induced inflammation, despite nuclear localization of p53, enhanced co-expression of type-I interferons (IfnbI) and the inflammasome sensor Aim2, both classic features of DNA-break-induced DDR activation. These effects were not observed in the livers of either infected group. Instead, in this tissue, the inflammatory response and DDR were associated with high oxidative stress-induced DNA damage.Our work highlights the relevance of the tissue microenvironment in enabling the typhoid toxin to suppress the host inflammatory response in vivo.